1999
DOI: 10.1128/mcb.19.12.8028
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Development and Cardiovascular Function Are Normal in Annexin VI Null Mutant Mice

Abstract: Annexins are calcium-binding proteins of unknown function but which are implicated in important cellular processes, including anticoagulation, ion flux regulation, calcium homeostasis, and endocytosis. To gain insight into the function of annexin VI, we performed targeted disruption of its gene in mice. Matings between heterozygous mice produced offspring with a normal Mendelian pattern of inheritance, indicating that the loss of annexin VI did not interfere with viability in utero. Mice lacking annexin VI rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 24 publications
7
58
0
Order By: Relevance
“…Annexin VI has been implicated as an important regulatory component of clathrin-mediated endocytosis (15)(16)(17)28), although the primary significance of the protein in this process remains unclear (29). Lin et al (28) used an in vitro system to demonstrate that annexin VI is required for the Ca 2ϩ -and ATP-dependent budding of clathrin-coated pits from membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin VI has been implicated as an important regulatory component of clathrin-mediated endocytosis (15)(16)(17)28), although the primary significance of the protein in this process remains unclear (29). Lin et al (28) used an in vitro system to demonstrate that annexin VI is required for the Ca 2ϩ -and ATP-dependent budding of clathrin-coated pits from membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, compensatory mechanisms were proposed to alleviate the loss of AnxA6 in vivo. However, while several annexins were found to be upregulated in the AnxA1 KO mice (Hannon et al, 2003), AnxA1, A2 and A5 protein levels in the heart, liver and spleen of the AnxA6 -/-mice remained unchanged (Hawkins et al, 1999). This indicated that at least these annexins were not upregulated to compensate for the loss of AnxA6 in these organs.…”
Section: Anxa6 Ko Micementioning
confidence: 91%
“…However, depending on the cell type analysed, several non-conventional secretion pathways seem to contribute to the cellular export of AnxA1 (Gerke et al, 2005;Perretti and D'Acquisto, 2009;Gavins and Hickey, 2012). After the successful generation of viable AnxA6 and AnxA7 KO strains (Hawkins et al, 1999;Herr et al, 2001; see below), Flower, Hannon and colleagues generated the AnxA1 KO mice (AnxA1 -/-) to provide proof-of-principle in vivo that AnxA1 confers glucocorticoid-dependent activation of innate immune cells to limit pro-inflammatory response (Hannon et al, 2003) (Table 2). AnxA1 KO mice were healthy and bred normally without obvious physical or behavioral difference compared to control animals.…”
Section: Anxa1 Ko Micementioning
confidence: 99%
See 1 more Smart Citation
“…In a prostate cancer model, downregulation of annexin A6 was observed during progression from a benign to a malignant state (K Rasiah and R Sutherland, personal communication); these findings suggest a tumour suppressor role for annexin A6 in malignant progression. However, despite reduced levels in cancer models, annexin A6 knockoutmice appear normal and do not develop spontaneous tumours (Hawkins et al, 1999;TG, unpublished results). These findings are similar to results for annexin A2 and A7, which are linked to cell growth and transformation (Checuti et al, 2001;Srivastava et al, 2001;Liu et al, 2003), but annexin A2 and A7 null animals do not develop tumours (Herr et al, 2001;Ling et al, 2004), suggesting that some annexins could functionally replace one another (reviewed in Gerke and Moss, 2002).…”
Section: Introductionmentioning
confidence: 90%